ANALISIS KECEPATAN ALIRAN HIDROGEN PEROKSIDA (H2O2) PADA STERILISASI SALURAN AKAR GIGI MENGGUNAKAN METODE NUMERIK VOLUME HINGGA - Hardiyanti, Siska Aprilia; Dafik, D; Fatahillah, Arif (KadikmA, 2015)
Abstract. The sterilization of tooth root canal is one of phases at treatment of endodontic or pulp treatment or commonly called tooth root canal treatment. This treatment is necessary because over the years many doctors assumed cavities tooth that cause pain and can not cure, should be pulled out. Endodontic treatment is the appropriate treatment for patient. Endodontic treatment is one of the measures to maintain the tooth in the mouth as long as possible when the pulp tissue has been infected. This research construct a model of tooth root canal and solve sterilization problem by using the finite volume method. Model of simulation process is solved using MATLAB and FLUENT software. The model which is constructed based on direction syringe spray and impeller pressure. Based on the result of the research, if angle of syringe spray is getting greater then the velocity is getting lower, if the angle of syringe spray is getting smaller then the velocity is getting higher. If the value of impeller pressure is more than 6 Pa then velocity is higher, if the value of impeller pressure is less than 6 Pa then velocity is negative value, whereas if the value of impeller pressure is 6 Pa then velocity is moderate value and the change of domain length of tooth root canal is not to great, so the spreading of velocity is evenly. Key Words : Treatment of endodontically, Sterilization of Root Canals, Angle of Syringe Spray, Impeller Pressure, Finite Volume Method.